2021
DOI: 10.4314/njt.v39i4.7
|View full text |Cite
|
Sign up to set email alerts
|

Use of expanded polystyrene from disposable food pack as a modifier for bitumen in hot mix asphalt

Abstract: This study evaluate the use of Disposable Food Pack (DFP) as a modifier for bitumen for an improved Hot Mix Asphalt (HMA). The  bitumen was modified with 2%, 4%, 6%, 8% and 10% DFP obtained from domestic waste. The penetration, ductility and specific gravity of DFP modified bitumen decreased from 68mm to 59.5mm, 110cm to 101cm and 1.025 to 1.012 respectively with increase in DFP, while softening point increased from 49.5 oC to 54.5 oC with increase in DFP. The Marshal Stability results revealed that the DFP mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
3
5
0
Order By: Relevance
“…This could be responsible for the decrease in penetration with the increase in the melted EPS content in the bitumen. This result agrees with the observations of [14,15,18] in which the penetration also decreased with the addition of EPS plastic wastes in ground form.…”
Section: Marshal Test Characteristicssupporting
confidence: 93%
See 1 more Smart Citation
“…This could be responsible for the decrease in penetration with the increase in the melted EPS content in the bitumen. This result agrees with the observations of [14,15,18] in which the penetration also decreased with the addition of EPS plastic wastes in ground form.…”
Section: Marshal Test Characteristicssupporting
confidence: 93%
“…Murana et al [18], used disposable food pack, a form of polystyrene to modify bitumen in hot mix asphalt and observed that with the increase in percentage by weight of the disposable food pack in bitumen there was a decrease in the penetration, ductility, flow and specific gravity while there was an increase in softening point and stability value. An optimum disposable food pack content of 6.7% by weight of the optimum bitumen content was obtained in the study.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, they have reported an increase in stiffness of the bitumen with waste PS according to penetration and softening point results. The raise in the stiffness is also supported by other studies [19][20][21]. Although several studies have been carried out on EPS modification of asphalt binder, no single study exists that uses statistical evaluation methods.…”
Section: Introductionmentioning
confidence: 53%
“…The waste EPS was added into the bowl, which contains 150°C hot bitumen, at certain percentages of bitumen weight ( 2%, 4%, 6%, and 8%). These ratios were selected based on previous studies where additive ratios are below 10% [16,[19][20][21]. Then, EPS and the bitumen mixed homogeneously.…”
Section: Methodsmentioning
confidence: 99%
“…It was concluded that the PS-modified binder could perform satisfactorily in hot weather and could be applied on playground surfaces, parking lots, and sidewalk pavements. Recycled polystyrene from waste disposable food packs (DFP) as a bitumen modifier for hot mix asphalt was investigated by Murana et al [18]. DFP obtained from household waste was mixed into the bitumen in proportions of 2%, 4%, 6%, 8%, and 10%.…”
Section: Introductionmentioning
confidence: 99%